Observation of Flow Loss on Pneumatic Fly Ash Transport System in Cement Plant - Muhammad Akhbar; Yolli Fernanda; Refdinal Refdinal; Arwizet K (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Pneumatic conveying is a material transport tool that utilizes compressed air in a pipe that comes from a blower or compressor. The EP dust raw mill material transport equipment is designed using the pneumatic conveying principle which aims to deliver the material optimally to the cement mill. Therefore, this study aims to analyze the fluid flow in the EP dust Raw Mill material transport system pipe which aims to determine the phenomenon of fluid flow in the pipe design and find the head loss of the material transport pipe. This analysis uses a numerical method that is solving problems by being formulated mathematically by calculating operations and assisted by solidworks software. The size of the pipe to be analyzed is 330 meters long with a diameter of 0.2 meters and has 8 elbows and a head loss of 425.53 meters is obtained, while the results of theoretical calculations obtained a major loss of 374.61 meters and a minor loss of 20.87 meters and the total head loss is 395.48 meters. Pneumatic conveying merupakan alat transpor material yang memanfaatkan udara bertekanan dalam pipa yang berasal dari blower maupun compressor. Alat transpor material EP dust raw mill dirancang menggunakan prinsip pneumatic conveying yang bertujuan untuk menghantarkan material secara optimal menuju cement mill. Oleh karena itu penelitian ini bertujuan untuk menganalisis aliran fluida yang berada didalam pipa sistem transpor material EP dust Raw Mill yang bertujuan untuk mengetahui fenomena aliran fluida pada desain pipa dan mencari head loss dari pipa transpor material tersebut. Analisis ini menggunakan metode numerik yaitu menyelesaikan permasalahan dengan diformulasikan secara matematis dengan cara operasi hitungan dan dibantu oleh software solidworks. Ukuran Pipa yang akan dianalisis sepanjang 330 meter dengan diameter 0,2 meter dan memiliki elbow sebanyak 8 buah dan didapatkan headloss sebesar 425,53 meter sedangkan dari hasil perhitungan teoritis didapatkan major loss sepanjang 374,61 meter dan minor loss sebesar 20,87 meter dan total head lossnya sebesar 395,48 meter.